Combining PLGA Scaffold and MSCs for Brain Tissue Engineering: A Potential Tool for Treatment of Brain Injury - Ling Zhou; Jiangyi Tu; Guangbi Fang; Li Deng; Xiaoqing Gao; Kan Guo; Jiming Kong; Jing Lv; Weikang Guan; Chaoxian Yang (Hindawi Limited, 2018)
Nerve tissue engineering is an important strategy for the treatment of brain injuries. Mesenchymal stem cell (MSC) transplantation has been proven to be able to promote repair and functional recovery of brain damage, and poly (lactic-co-glycolic acid) (PLGA) has also been found to have the capability of bearing cells. In the present study, to observe the ability of PLGA scaffold in supporting the adherent growth of MSCs and neurons in vivo and vitro and to assess the effects of PLGA scaffold on proliferation and neural differentiation of MSCs, this study undertakes the following steps. First, MSCs and neurons were cultured and labeled with green fluorescent protein (GFP) or otherwise identified and the PLGA scaffold was synthesized. Next, MSCs and neurons were inoculated on PLGA scaffolds and their adhesion rates were investigated and the proliferation of MSCs was evaluated by using MTT assay. After MSCs were induced by a neural induction medium, the morphological change and neural differentiation of MSCs were detected using scanning electron microscopy (SEM) and immunocytochemistry, respectively. Finally, cell migration and adhesion in the PLGA scaffold in vivo were examined by immunohistochemistry, nuclear staining, and SEM. The experimental results demonstrated that PLGA did not interfere with the proliferation and neural differentiation of MSCs and that MSCs and neuron could grow and migrate in PLGA scaffold. These data suggest that the MSC-PLGA complex may be used as tissue engineering material for brain injuries.